Uso de dietas artificiales para la cria de larvas y adultos de Ceraeochrysa cubana (Hagen) (Neuroptera: Chrysopidae) - Vargas Serrano, G.=700 1 Luque, J.E.; Villanueva, A.
(En, Es)
Ilus., 10 ref.
Keywords: NEUROPTERA; CHRYSOPIDAE; INSECTA; DIETA TERAPEUTICA; ALIMENTOS ARTIFICIALES; LARVAS; FERTILIDAD; LONGEVIDAD; COLOMBIA; CARAEOCHRYSA CUBANA; AGRONOMIA COLOMBIANA